Strategies’ Formulation for Empowering Tengger Tribe Women Farmers in Probolinggo Regency - Siti Alimah; Sumarningsih; Dwiyana Anela Kurniasari; Agus Subhan Prasetyo; Reyhan Raj Bima Saputra (Jurnal AGRISEP, 2025)
The 5th Sustainable Development Goal (SDG) focuses on gender issues, including women's roles in politics and the economy. In the financial sector, women contribute to agriculture, but gender inequalities persist, requiring gender-oriented empowerment programs to address disparities in the potato sub-sector. This research analyzes the role of Tengger Tribe women farmers using Gender Framework Analysis (GFA) and formulates strategies for their empowerment. The study was conducted in the Tengger Tribe community, Sukapura Village, Probolinggo Regency, using a census method with 78 women rice farmers as respondents. Data collection involved observation, in-depth interviews, and questionnaires. The first objective was analyzed using qualitative descriptive methods, the second through gender analysis to assess workloads in potato production, followed by social capital analysis and SWOT analysis. The strategy results include (1) establishing a women farmers' group in Sukapura Village with stakeholder facilitation, (2) training and assistance in food crop cultivation suited to local conditions, and (3) organizing a women's farming school to enhance farmers' knowledge. Policy implications for this empowerment strategy should consider various aspects, including beneficial innovations for women farmers in Sukapura Village and mechanisms for implementing and financing empowerment initiatives.